Protein refolding in an oscillatory flow reactor - Lee, CT (Springerlink, 2001)
We demonstrate that an oscillatory flow reactor is a viable reactor for protein refolding via direct dilution. The mixing characteristics of the oscillatory flow reactor are well described and controllable and, importantly, can be scaled-up to process scale without a loss of mixing efficiency. This makes the oscillatory flow reactor an attractive alternative to conventional stirred-tank reactors for process-scale renaturation.